TRAINING OF THE PASS TECHNIQUE IN YOUTH CATEGORY FOOTBALL PLAYERS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Players in the youth category have some shortcomings when passing the ball in short, mediumand long distance, which prevents the team from taking effective technical and tactical actions inthe game. Given the present needs, the following is formulated: How to improve the passingtechnique in youth category footballers? With the aim of providing an answer, the objective is to:Identify the main deficiencies in the passing technique of soccer players in the youth category ofthe Champion's Claw soccer school. Within the methodology, the qualitative-quantitative methodhas been considered. The application of a diagnostic test composed of 10 exercises subject totimes and successes, allowed to know the current state of practice in the technique of passing theyouth category. The techniques belong to the exploratory nature, in order to get to know directlyfrom those involved. In an identical way the field research provided an insight into the soccerschool students. The population involved for this study is made up of 35 men and 15 women whobelong to the soccer school. From this population group, an intentional non-probabilistic samplewas drawn, consisting of 10 men and 8 women. The results showed that the test participantsqualitatively the majority border the fair and good. As a conclusion, it is proposed that the youthsoccer team of the Champion's Claw School, through the practice of a structure, exercise andactivities, would improve its current condition.